Peran Strategis Modal Ventura Syariah dalam Mempercepat Pertumbuhan Startup dalam Lanskap Ekonomi Digital - Ichfan, Hoirul; Wahyudi, Ilham (Moderasi : Journal of Islamic Studies, 2024)
The development of the digital economy has created new opportunities for the emergence of technology- and innovation-based startups. However, limited access to financing is a major challenge to the growth and sustainability of startups, especially in the early stages. Sharia venture capital offers a strategic solution by providing high-risk financing coupled with managerial support, network access, and business mentoring. This article aims to analyze the strategic role of Sharia venture capital in accelerating startup growth in the digital economy landscape, reviewing its contribution to growth, challenges faced, and future prospects. The method used is a literature review with a qualitative-descriptive approach. The results of the study indicate that Sharia venture capital serves not only as a source of funding but also as a catalyst for innovation and a business accelerator. However, challenges such as unequal access, high risk, and incomplete regulations remain obstacles to optimizing the role of Sharia venture capital in Indonesia. Therefore, collaboration between the government, industry players, and financial institutions is key to creating a healthy and sustainable startup financing ecosystem